EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TALKING STICK TERHADAP MOTIVASI BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM MATERI SEJARAH KHULAFAURRASYIDIN DI KELAS V SDN CINUNUK 01 BANDUNG - Haditsa Qur'ani Nurhakim; Alvia Sabrina; Ayi Sobarna; Aep Saepudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by low student learning motivation and less than optimal teacher skills in implementing the learning model at SDN Cinunuk 01 Bandung. This research aims to measure the level of student learning motivation in Islamic Religious Education subjects, especially the historical material Getting to Know Khulafaurrasyidin, by applying the Talking Stick cooperative learning model. Apart from that, this research also aims to determine the differences in learning motivation between the experimental class and the control class. This research uses a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The research sample involved class V-B as the experimental class and one other class as the control class. The results showed that students' learning motivation in the control class did not experience a significant increase and remained at a moderate level. Before the treatment, the average score for learning motivation was 120.77, while after the treatment it increased to 141.63. The learning motivation of students in the experimental class increased significantly to reach a high level. Before treatment, the average score for learning motivation was 121.20, and after being given the Talking Stick cooperative learning model, it increased to 157.80 and the effectiveness of increasing learning motivation between the experimental class and the control class was proven through t test analysis. The analysis results show that the calculated t value is greater than the t table (15.492 > 2.002), so that H₀ is rejected and H₁ is accepted. This indicates that there is a difference in the average post-test learning motivation between the experimental class and the control class. From the research results, it can be concluded that the Talking Stick cooperative learning model is effective in increasing students' learning motivation in Islamic Religious Education subjects, especially in the Getting to Know Khulafaurrasyidin material.